Sustainable Biodiesel: Kinetic Study and Modeling of Catalytic Esterification of Used Vegetable Oils as The First Stage of the Production Process - Rodriguez, Verónica (2017)
In an attempt to satisfy the needs for sustainable production of biofuel in industrial processes, thepresent work develops the esterification kinetics of used vegetable oils (UVOs) with ethanol,employing acidified sunflower oil. The process was carried out in a thermostated batch reactor withmagnetic stirring. Different temperatures (50ºC, 60ºC and 70°C) and reaction times in the range 0-90minute were assayed. An ethanol/oleic acid molar ratio of 60:1 was applied. The catalyst used wasH2SO4 (5% w / w relative to the free fatty acid). A conversion of 75.54% was determined at 70 °C.These experimental kinetic data were used in the simulation of the complete esterification processperformed in Aspen HYSYS with similar conversion results.